205k views
5 votes
Given f(x) = 6x + 2, find f(x – 3).

A. f(x – 3) = 6x – 1
B. f(x – 3) = 6x – 16
C. f(x - 3) = x - 1
D. f(x – 3) = 6x2 – 16x - 6

User Roth
by
5.9k points

1 Answer

1 vote

Answer: B. f(x - 3) = 6x - 16

Concept:

When encountering a question that gives you a function and the evaluation value, then basically plug the given value into the function.

Solve:

Given function and value

f(x) = 6x + 2

f(x - 3)

Substitute the value into the given expression

f(x - 3) = 6 (x - 3) + 2

f(x - 3) = 6x - 18 + 2

f(x - 3) = 6x - 16

Hope this helps!! :)

Please let me know if you have any questions

User Greyaurora
by
5.8k points